Acute toxicity study of antibacterial organophilic bentonite incorporated with geranyl acetate in mice and geranyl acetate liberation in simulated gastric fluid. (1st March 2023) - Capelezzo, A.P.; Celuppi, L.C.M.; Kuhn, K.Z.; Sanaiotto, O.; Scapinello, J.; Zanetti, M.; Zeferino, R.C.F.; Müller, L.G.; Fiori, M.A.; Riella, H.G.
Abstract: In the present study, the antibacterial property of the organophilic bentonite (Bent-ODA) and organophilic bentonite incorporated with geranyl acetate ester (Bent-ODA-GA) was evaluated against bacteria Staphylococcus aureus, Escherichia coli and Salmonella typhimurium . Oral acute toxicity of Bent-ODA-GA was evaluated in mice, by a single oral dose of 300 and 2000 mg kg −1 . Animals were observed for any toxicity clinical signs or mortality for 15 days according to OECD 423 guidelines. The release assay of GA presents in Bent-ODA in simulated gastric fluid, pH 3.5 and pH 6.5 was also performed. Bent-ODA-GA composite presented antibacterial activity against S. aureus and S. typhimurium bacteria with 10.7 ± 0.6 mm and 2.2 ± 0.1 mm inhibition halo, respectively, which make it possible to associate the composite antimicrobial feature due to the ester presence. The composite did not reveal any toxicity signs or mortality in any animal for acute toxicity treatment during the 15 days observation period. The LD50 of Bent-ODA-DA was estimated to be greater than 2000 mg kg −1 . It was also observed that geranyl acetate is released from Bent-ODA in concentrations lower than 0.03 mg kg −1 for pH 3.5 and 0.004 mg kg −1 for pH 6.5, which are lower than those that could cause some toxic effects in animals. Graphical abstract: Image 1 Highlights: Bent-ODA-GA was able to inhibit the growth or cause the death of bacteria. Bent-ODA-GA did not cause the death of animals when submitted to the acute toxicity test. In simulated gastric fluid, low concentrations of GA are released from Bent-ODA.